2016
DOI: 10.1016/j.bbrc.2016.08.159
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of toll-like receptor stimulation on mRNA-driven myogenic conversion of human and mouse fibroblasts

Abstract: Transfection with in vitro transcribed mRNAs is a safe and effective tool to convert somatic cells to any cell type of interest. One caveat of mRNA transfection is that mRNAs are recognized by multiple RNA-sensing toll like receptors (TLRs). These TLRs can both promote and inhibit cellular reprogramming. We demonstrated that mRNA transfection stimulated TLR3 and TLR7 and induced cytotoxicity and IFN-β expression in human and mouse fibroblasts. Furthermore, mRNA transfection induced paracrine inhibition of repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…5 D, bottom). In summary, our results confirmed previous observations that modified IVT mRNA does not activate intracellular pattern recognition pathways 34 .
Figure 5 Expression and functionality of NTCP protein dependent on the dose of ICT mRNA.
…”
Section: Resultssupporting
confidence: 92%
“…5 D, bottom). In summary, our results confirmed previous observations that modified IVT mRNA does not activate intracellular pattern recognition pathways 34 .
Figure 5 Expression and functionality of NTCP protein dependent on the dose of ICT mRNA.
…”
Section: Resultssupporting
confidence: 92%
“…One possibility is suggested by reports that activation of antiviral or pro-inflammatory pathways, which still occurs at a low level even when countermeasures like modified mRNA and B18R are employed, might actually facilitate reprogramming. [38][39][40][41] If this idea is valid, the window in which such benign effects outweigh the cytotoxic and cytostatic effects of innate immune stimulation must be quite narrow. It also seems possible that collective effects involving cellcell communication are at work, linked to the homogeneity of factor expression achieved in the mRNA system-a speculative hypothesis prompted by the lockstep, population-wide phenotypic shifts characteristic of mRNA reprogramming cultures.…”
mentioning
confidence: 99%
“…Although a very low level of inflammation may occur when modRNA and B18R were applied, this might facilitate reprogramming. Reports showed that deliberate control of TLR signaling-mediated inflammation is critical in the success of mRNA-induced somatic reprogramming [ 122 , 123 , 124 , 125 ].…”
Section: Safetymentioning
confidence: 99%